How optimal are the extremes? Latin American exchange rate policies during the Asian crisis - Ricardo Ffrench-Davis; Guillermo Larraín (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
During the Asian crisis, intermediate exchange rate regimes vanished. It has been argued that those regimes were no longer useful and only the extremes remained valid. The paper analyses three foreign exchange regimes: Argentina (pegged), Chile (band) and Mexico (float). The Argentinean currency board delivered low financial volatility while it was credible, but even then it displayed high real volatility. Mexican float performed well in periods of instability isolating the real sector. The Chilean band delivered a mixed outcome as compared to Argentina and Mexico. This is linked apparently to a loss in the band's credibility, associated to policy mismanagement and an over-appreciation in the biennium before the crisis. Optimal exchange rate regimes vary across time and the conjuncture. Exit strategies are part of the election of the optimal system, including a flexible policy package rather than a single rigid policy tool.
Keywords: E61; E65; F31; F41; 330; exchange rate; crawling-bands; currency boards; macroeconomic sustainability; Latin America; Wechselkurspolitik; Wechselkurssystem; Currency Board; Lateinamerika